The Influence of Motivation and Competence on Employee Performance Through Job Satisfaction - R. Rosmawati; Syamsul Alam; Yana Fajriana (Manunggal Halim Jaya, 2025)
The digital transformation in university administrative governance, through the implementation of the E-Office system, requires administrative staff to possess adequate technical competencies and strong work motivation. However, in practice, not all employees can adapt optimally, which affects their job satisfaction and performance. This study aims to analyze the effect of motivation and competence on employee performance, with job satisfaction serving as a mediating variable, at the Faculty of Engineering, Hasanuddin University. This research employed a quantitative approach, utilizing a survey method with 51 respondents, and the data were analyzed using Structural Equation Modeling (SEM). The results indicate that motivation and competence do not have a direct effect on employee performance. However, job satisfaction has a positive and significant effect on performance. Moreover, motivation and competence have a positive influence on job satisfaction, which subsequently mediates the effect of motivation and competence on employee performance. These findings highlight that job satisfaction plays a crucial role in enhancing employee performance, suggesting that efforts to improve motivation and strengthen competence should focus on fostering higher job satisfaction.